Some remarks on the multiple partners game; The existence of stable matchings for the marriage market: a non-constructive elementary proof. (a note) - Sotomayor, Marilda (2021)
Conteúdo: 1. Some remarks on the multiple partners game. 2. The existence of stable matchings for the marriage market: a non-constructive elementary proof. (a note)